Utilization of pineapple cobs and peels for fruit leather processing - Rosida; Ulya Sarofa; Anggraeni Putri Pertiwi (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Pineapple cobs and peels are agricultural waste that have not been utilized optimally, but still have a high nutritional content including carbohydrates and proteins, and contain phenolic compounds and flavonoids. Efforts to utilize the waste of pineapple cob and peels by processing it into fruit leather to increase its economic value. The purpose of this study was to determine the effect of the proportion of cobs: pineapple peel and the addition of carrageenan on product quality, and to determine the best treatment to produce fruit leather with good characteristics and be liked by the panelists. This study used a completely randomized design (CRD) with a two-factor factorial pattern with two replications. Factor I was the proportion of tubers: pineapple peels (w/w) 60:40, 50:50, and 40:60. Factor II was carrageenan concentration of 0.6%, 0.8% and 1%. Based on the results of the study, the best treatment was the proportion of cobss: pineapple peels 50:50 (w/w) with a carrageenan concentration of 1% which produced fruit leather with a water content of 16.26%, reducing sugar content of 24.83%, vitamin C content of 15 .37 mg/100g, antioxidant activity 27.37%, crude fiber content 3.08%, and tensile strength 3.02 N.